Warenhuis: Symbol of Modernity and Economic Transformation of Medan in 20th Century - Rismawati Br Sagala; Rangga Handoko; Nur Ardina Khoirunnisa; Tiar Meidayani Pasaribu; Yushar Tanjung (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This study investigates the Warenhuis—Medan’s first modern department store—as both a symbol of colonial-era modernity and a pivotal force in the city’s economic transformation during the Dutch East Indies period. Strategically located at the confluence of European urban planning and local commercial dynamics, the Warenhuis served not only as a site for retail activity but also as a visual and functional embodiment of socio-economic change within a rapidly industrializing colonial context. The central inquiry guiding this research is: in what ways did the emergence and operation of the Warenhuis mirror and shape Medan’s economic and spatial development during the colonial era? Using a qualitative historical methodology, the research draws upon archival sources, colonial-era newspapers, and urban planning documents to trace the department store’s role in reshaping the city’s commercial infrastructure. The findings reveal that the Warenhuis operated as more than a commercial establishment—it acted as a cultural and economic interface, where colonial ideologies of progress intersected with indigenous modes of consumption and space-making. It simultaneously symbolized colonial ambition and enabled capitalist expansion, contributing significantly to the formation of Medan’s modern urban identity in the early 20th century.